2018
DOI: 10.1002/aoc.4366
|View full text |Cite
|
Sign up to set email alerts
|

Crystal packing, vibrational studies, DFT calculations of a new hybrid nickel (II)‐complex and its application in Heck and Sonogashira cross‐ coupling reactions

Abstract: 4 ]SO 4 that it was hydrothermally synthesized by reaction of 5,5'-dimethyl-2,2'-bipyridne, denoted (dmbpy), metal salt and sulfuric acid. The large crystals are characterized by X-ray single crystal diffraction, infrared, Raman spectroscopy and DFT calculation. The thermogravimetric analysis indicated that the dehydration occurs in two steps, leading to an anhydrous compound. At room temperature, the complex crystallises in the centrosymmetric space group P2 1 /c with the following parameters a = 9.492 (7) Å,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Nowadays, transition metal complexes are attracting wide attention not only because of their intriguing variety of architectures and molecular topologies [1][2][3][4][5], but also but also these new materials are also sought for improved optical, and electrical properties, magnetic, medicinal, luminescence and ionic conductivity, as well as chemical or biochemical activity [6][7][8][9][10][11][12][13][14][15][16][17]. A good example among these promising complexes is when Cu(II) is the central metal, since copper complexes have been reported to show versatile properties and applications [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, transition metal complexes are attracting wide attention not only because of their intriguing variety of architectures and molecular topologies [1][2][3][4][5], but also but also these new materials are also sought for improved optical, and electrical properties, magnetic, medicinal, luminescence and ionic conductivity, as well as chemical or biochemical activity [6][7][8][9][10][11][12][13][14][15][16][17]. A good example among these promising complexes is when Cu(II) is the central metal, since copper complexes have been reported to show versatile properties and applications [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, at an amplitude value of 40%, the obtained yield decreased, which seems to correspond to the threshold of the physical limit of the ultrasonic activation. [46,47] The effect of ultrasound increased with the amplitude used until a maximum value, which is the cavitation threshold. From this level, the cavitation is very intense.…”
Section: Sonogashira Reactionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Moreover, a large number of studies showed that postsynthetic functionalization or direct syntheses with ligands having suitable functionality can impart hydrogen bond capabilities to the organic-inorganic hybrid. 24,25 Besides, one of the most widely studied functional groups that have been used to impart hydrogen bonding capabilities to the hybrid is the amino, carbonyl, anhydride, cyano group, etc., [26][27][28][29][30] Even more recently, the self-assembly processes are sensitive to diverse synthetic conditions in some cases, change of reaction conditions such as the solvent, pH and temperature for a given set of organic ligands and metal ions can cause various supramolecular architectures. 31,32 In this regard, solvent molecules or counter-ions (CH3COO -, NO3, NO2, ClO4 -, etc) may also dramatically influence the overall solid-state architecture Please do not adjust margins Please do not adjust margins by participating in metal coordination and hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%